Early Subretinal Allograft Rejection is Characterized by Innate Immune Activity - Kevin P. Kennelly (Cell Transplantation, 2017)
Successful subretinal transplantation is limited by considerable early graft loss despite pharmacological suppression of adaptive immunity. We postulated that early innate immune activity is a dominant factor in determining graft survival and chose a nonimmunosuppressed mouse model of retinal pigment epithelial (RPE) cell transplantation to explore this. Expression of almost all measured cytokines by DH01 RPE cells increased significantly following graft preparation, and the neutrophil chemoattractant KC/GRO/CINC was most significantly increased. Subretinal allografts of DH01 cells (C57BL/10 origin) into healthy, non immunosuppressed C57BL/6 murine eyes were harvested and fixed at 1, 3, 7, and 28 days postoperatively and subsequently cryosectioned and stained. Graft cells were detected using SV40 large T antigen (SV40T) immunolabeling and apoptosis/necrosis by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL). Sections were also immunolabeled for macrophage (CD11b and F4/80), neutrophil (Gr1 Ly-6G), and T-lymphocyte (CD3-∊) infiltration. Images captured with an Olympus FV1000 confocal microscope were analyzed using the Imaris software. The proportion of the subretinal bolus comprising graft cells (SV40T + ) was significantly ( p < 0.001) reduced between postoperative day (POD) 3 (90 ± 4%) and POD 7 (20 ± 7%). CD11b + , F4/80 + , and Gr1 Ly-6G + cells increased significantly ( p < 0.05) from POD 1 and predominated over SV40T + cells by POD 7. Colabeling confocal microscopic analysis demonstrated graft engulfment by neutrophils and macrophages at POD 7, and reconstruction of z-stacked confocal images confirmed SV40T inside Gr1 Ly-6G + cells. Expression of CD3-∊ was low and did not differ significantly between time points. By POD 28, no graft cells were detectable and few inflammatory cells remained. These studies reveal, for the first time, a critical role for innate immune mechanisms early in subretinal graft rejection. The future success of subretinal transplantation will require more emphasis on techniques to limit innate immune-mediated graft loss, rather than focusing exclusively on suppression of the adaptive immune response.